ANALISA PENGENDALIAN PERSEDIAAN BAHAN BAKU DENGAN MENGGUNAKAN METODE ECONOMIC ORDER QUANTITY, SAFETY STOCK DAN REORDER POINT - Febrianti Gresia Putri Handi; Dwiki Fransiska Sinaga; Anita Christine Sembiring (Universitas Stikubank, 2026)
This research is driven by the high risk of production disruptions at PT. Central Proteina Prima Tbk. due to the uncertain availability of rice bran and wheat bran pollard raw materials. Inefficient inventory management potentially leads to inflated holding costs (overstock) or operational shutdowns caused by stockouts; therefore, optimized inventory control is essential. Utilizing a quantitative approach through the Economic Order Quantity (EOQ) method, this study determines the optimal order quantity while calculating Safety Stock (SS) and the Reorder Point (ROP)—with a 5-day lead time assumption—to maintain stock stability. Analysis of a 12-week period involving the consumption of 61.2 tons of rice bran and 40.8 tons of wheat bran pollard yielded specific technical parameters: for rice bran, a safety stock of 14.52 tons and an ROP of 18.16 tons; and for wheat bran pollard, a safety stock of 17.2 tons and an ROP of 19.59 tons. Overall, the integrated application of EOQ, SS, and ROP methods is proven effective in enhancing cost efficiency and ensuring the optimal continuity of the company's production processes.